ANALYSIS OF THE NUTRITIONAL PROFILE AND LIFESTYLE OF THE ELDERLY AND THE CORRELATION WITH NON-COMMUNICABLE CHRONIC DISEASES (CIPEEX, 2025)
Objective: To identify risk factors related to the nutritional profile and lifestyle of elderly people for the development of non-communicable chronic diseases (NCDs). Method: This is an integrative review. Article searches were performed in the National Library of Medicine and National Institutes of Health (PubMed), Virtual Health Library (VHL), and Google Scholar databases. Results: Nutritional profile, lifestyle, elderly, and body weight were risk factors for the occurrence of NCDs. Conclusion: It is essential to identify risk factors for the occurrence of chronic diseases. This analysis is crucial to provide support for professional practice and to generate information that can substantiate and improve the health strategies of elderly support centers.
Keywords: Nutritional Profile; Lifestyle; Elderly